LONGTERM CHANGES IN SPE CIES COMPOSITION OF SWISS BEECH FORESTS - WALTHER, G.R. (Annali di Botanica, 1997)
Even in so called undisturbed forest ecosystems there have always been all sorts of changes in structure and species composition going on. The presented study tries to distinguish between natural changes in species composition due to the natural forest life-cycle and new occurring, possibly man induced changes in forest vegetation, which have happend within the last thirty years. General trends have been elaborated and different causes drawn up. More detailed results concerning beech forest are presented and discussed in a broader context with other recent studies conducted in Europe to the same topic.